2015
DOI: 10.1176/appi.ajp.2014.14020173
|View full text |Cite
|
Sign up to set email alerts
|

The STRIDE Weight Loss and Lifestyle Intervention for Individuals Taking Antipsychotic Medications: A Randomized Trial

Abstract: Objectives STRIDE assessed whether a lifestyle intervention, tailored for individuals with serious mental illnesses, reduced weight and diabetes risk. Methods A multi-site, parallel, two-arm randomized controlled trial in community settings and an integrated health plan. Inclusion criteria: Age ≥18; taking antipsychotic medication for ≥30 days; BMI ≥27. Exclusions: significant cognitive impairment; pregnancy/breastfeeding; recent psychiatric hospitalization, bariatric surgery, cancer, heart attack or stroke.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
224
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(239 citation statements)
references
References 41 publications
5
224
3
3
Order By: Relevance
“…Although the probability of attaining normal body weight is low for individuals who are obese (Fildes et al 2015), significant reductions in cardiovascular risk factors can be attained from modest amounts of weight loss (Wing et al 2011). A series of randomized controlled trials of lifestyle interventions have demonstrated that individuals with SMI can achieve clinically significant weight loss by making positive changes in diet and exercise Daumit et al 2013;Green et al 2015). However, the long-term maintenance of weight loss remains elusive for the vast majority of obese individuals, even among those who receive gold standard behavioral treatments (Diabetes Prevention Program Research 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the probability of attaining normal body weight is low for individuals who are obese (Fildes et al 2015), significant reductions in cardiovascular risk factors can be attained from modest amounts of weight loss (Wing et al 2011). A series of randomized controlled trials of lifestyle interventions have demonstrated that individuals with SMI can achieve clinically significant weight loss by making positive changes in diet and exercise Daumit et al 2013;Green et al 2015). However, the long-term maintenance of weight loss remains elusive for the vast majority of obese individuals, even among those who receive gold standard behavioral treatments (Diabetes Prevention Program Research 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, adult weight management programs located within community mental health clinic settings have been successfully implemented. [17][18][19] Although the available evidence base in this area is limited, a small number of studies suggest that factors specifically related to psychiatric illness, including behavioral symptoms (e.g., social anxiety, paranoia, and lack of initiative), medication effects (sedation and excessive weight gain preventing physical mobility), and lack of transportation or social support often prevent mentally ill adults from engaging in weight loss treatment. 20,21 Programming that increases health knowledge and that offers social engagement and daily structure is cited as promoting engagement in behavioral weight loss programs.…”
mentioning
confidence: 99%
“…Patients with mental health issues should be encouraged to participate in health improvement activities including weight management, physical activity, smoking cessation [28] and health care needs to be tailored to the individual [28]. A combination of motivational and behaviour change interventions, alongside appropriate pharmacological treatments, appear to provide the best results in terms of both health gain and adherence to health improvement activities.…”
Section: Resultsmentioning
confidence: 99%